2007
DOI: 10.1038/sj.leu.2404511
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent synergy of the proteasome inhibitor bortezomib and cytarabine in mantle cell lymphoma

Abstract: Single-agent bortezomib, a potent, selective and reversible inhibitor of the 26S proteasome, has demonstrated clinical efficacy in relapsed and refractory mantle cell lymphoma (MCL). Objective response is achieved in up to 45% of the patients; however, complete remission rates are low and duration of response proved to be short. These limitations may be overcome by combining proteasome inhibition with conventional chemotherapy. Here we present two case reports and in vitro data suggesting synergistic efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 24 publications
3
39
0
1
Order By: Relevance
“…Because its response rate is still low, a rationally combinational therapy would be the next step. Similarly, Weigert et al 18 performed in vitro studies and showed a sequencedependent synergy between BTZ and cytarabine in MCL. Their data suggest that pretreatment with cytarabine followed by proteasome inhibition may be a preferred approach.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Because its response rate is still low, a rationally combinational therapy would be the next step. Similarly, Weigert et al 18 performed in vitro studies and showed a sequencedependent synergy between BTZ and cytarabine in MCL. Their data suggest that pretreatment with cytarabine followed by proteasome inhibition may be a preferred approach.…”
Section: Discussionmentioning
confidence: 87%
“…We chose the BRC combination based on the effects of its single-agent activity and potential synergistic effect with other agents. [18][19][20] RTX has been used in clinical trials in newly-diagnosed and relapsed or refractory MCL, with ORR of 37%. 21 At M. D. Anderson Cancer Center, our upfront therapy for MCL is R-HyperCVAD/R-Methotrexate-Cytarabine.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were performed in triplicate and independently repeated 2 or 3 times. As previously described (12), the effects of sequential combination treatment were analyzed according to the Chou and Talalay method by using XLfit software (ID Business Solutions Ltd.) and evaluated using a combination index (CI) interpreted as: <0.7, synergistic; 0.7-1.3, additive; >1.3, antagonistic (13)(14)(15).…”
Section: In Vitro Cell Proliferation-inhibition Assays Of Monotherapymentioning
confidence: 99%
“…23 Thus, bendamustine-containing combinations or molecular-targeted approaches that have shown high response rates among patients with relapsed mantle-cell lymphoma might be alternative induction regimens. 22,[24][25][26] Similarly, it may be attractive to combine the rituximab-based maintenance regimen with other drugs that have been shown to be active against mantle-cell lymphoma. However, physicians need to be aware of the potential interactions between the initial therapy and the maintenance regimen.…”
Section: Discussionmentioning
confidence: 99%